Biocompatibility of Intracanal Medications Based on Calcium Hydroxide. (18th December 2012) - Andolfatto, Carolina; da Silva, Guilherme Ferreira; Cornélio, Ana Livia Gomes; Guerreiro-Tanomaru, Juliane Maria; Tanomaru-Filho, Mario; Faria, Gisele; Bonetti-Filho, Idomeo; Cerri, Paulo Sérgio
Abstract : Objective . The aim of this study was to evaluate the rat subcutaneous tissue reaction to calcium hydroxide-based intracanal medicaments, UltraCal XS (calcium hydroxide, barium sulphate, aqueous matrix), Hydropast (calcium hydroxide, barium sulphate, and propyleneglycol), and Calen (Calcium hydroxide, zinc oxide, colophony, and polyethyleneglycol), used as a control. Methods . Forty-eight rats ( Rattus Norvegicus Holtzman ) were distributed in three groups: Calen, UltraCal XS, and Hydropast. Polyethylene tubes filled with one of the medicaments were implanted in the dorsal subcutaneous. After 7 and 30 days, the implants were removed and the specimens were fixed and embedded in paraffin. Morphological and quantitative analyses were carried out in the HE-stained sections. The numerical density of inflammatory cells in the capsule was evaluated and statistical analyses were performed (P ≤ 0.05 ). Results . At 7 days, all materials induced an inflammatory reaction in the subcutaneous tissue adjacent to the implants. In all groups, a significant reduction in the number of inflammatory cells and giant cells was verified in the period of 30 days. Conclusion . These results indicate that the calcium hydroxide-based medicaments evaluated present biocompatibility similar to Calen.